Closing the gender digital divide, opening opportunities for women in agriculture - Bafana, Busani; Hosenally, Nawsheen (Technical Centre for Agricultural and Rural Cooperation, 2019)
Information and communication technologies (ICTs) are promoted as an equaliser of opportunities – but this is not always the case for women. Several African initiatives are demonstrating the critical contribution that information and knowledge can make to increase agricultural productivity and run a profitable agribusiness.